JURIDICAL ANALYSIS OF THE APPLICATION OF ARTICLE 170 PARAGRAPH (1) OF THE INDONESIAN CRIMINAL CODE IN THE CRIME OF COLLECTIVE VIOLENCE (A STUDY OF DECISION NUMBER 1935/PID.B/2025/PN MDN) - Taslim; Halimatul Maryani (CV. Barokah Publsiher, 2026)
Criminal Code (KUHP) in the crime of collective violence, to examine the legal construction of violence committed by joint force from the perspective of positive Indonesian criminal law, and to analyze the legal reasoning of judges in rendering a decision in Case Number 1935/Pid.B/2025/PN Mdn. The results of the study show that the application of Article 170 paragraph (2) point 1 of the KUHP, which provides for a maximum imprisonment of seven years if the offender intentionally damages property or if the violence used results in injuries, has been carried out appropriately, as all elements of the offense were proven lawfully and convincingly. The legal construction of the crime of violence committed by joint force places the element of collective action as the primary aggravating factor without requiring a detailed division of roles. The judges’ legal considerations in this case reflect a balance between juridical, sociological, and philosophical aspects, taking into account the protection of victims, the social impact of the act, and fairness for the defendants. Accordingly, the decision can be legally justified and reflects the objectives of sentencing within the framework of positive Indonesian criminal law.